EFL Teachers’ Perceptions of Continuing Professional Development: A Case of Iranian High School Teachers - Goudarz Alibakhshi (Profile: Issues in Teachers' Professional Development, 2015)
English, particularly regarding a foreign language teachers’ professional development, has been studied in depth. However, it is not known how Iranian English as a foreign language teachers perceive con - tinuing professional development. This study explored the perceptions of Iranian English as a foreign language teachers of continuing professional development and identified their main professional de - velopment activities. For the study, a phenomenological research design was applied. Twenty English teachers were interviewed. The data were content analyzed in line with the Randor model. The results showed that the participants perceived continuing professional development to entail skills develop - ment, continuous learning, keeping up to date, learning for interest, and professional revitalization. Ad - ditionally, they developed professionally through work, formal education, and attending and presenting at continuing professional development events.